The settlement analysis of shallow foundation on treated clay soil - Mohamad Shukry B. Amiry (School of Environmental Engineering, University Malaysia Perlis, 2014)
This project is to understand and discuss the properties of soil and sediment that occur on untreated clay and clay that has been treated. This study was to investigate the effect of sediment that occurs over clay -treated and untreated. This is very important and should take note because when shallow foundations on clay this can cause damage to the building structure and can cause buildings to collapse.